PROYEKSI SPASIAL UNDER BOUNDED CITY DI KOTA JAMBI BERBASIS SMCE CA (SPATIAL MULTY CRITERIA EVALUATION CELLULAR AUTOMATA) - Wicaksono, Dominikus Rinto Adhi (Magister Pembangunan Wilayah dan Kota,Undip, 2019)
At present 50% of the world's population lives in urban areas and it is estimated that in 2025 the Indonesian population living in urban areas is 68%. The tendency of people to stay near the city center caused a physical expansion in the suburbs. Jambi City as one of the big cities on the island of Sumatra also experienced physical development of the city with a high rate of development in the periphery to penetrate the jurisdiction (under bounded city) to the territory of the authority of Muaro Jambi Regency. Therefore, the physical development of Jambi City in the future needs to be predicted to overcome various problems that can occur related to urbanization, one of which is the threat of potential conversion of paddy fields and dryland agriculture in Muaro Jambi Regency which is directly adjacent to Jambi City. Dynamic modeling of urban expansion can be described by applying the Spatial Multi Criteria Evaluation Cellular Automata algorithm (SMCE CA). The analysis used included identification of trends in the physical development of Jambi City, identification of determinants of city physical development, Spatial Multi Cellular Automata Criteria Evaluation (SMCE CA) modeling, and model validation. Validation of modeling results shows overall accuracy of 92.5% and kappa value of 0.8369. Observation of the growth trend of the city of Jambi in the period 2000 to 2016 showed that the growth of built-up land was 295.1 hectares per year. The results of the spatial projection of the physical development of Jambi City in 2033 show the direction of the development of Jambi City to Muaro Jambi Regency with the dominance of growth to the west towards Jambi Luar Kota District with a growth rate of 159.2 hectares per year, to the southeast towards Sungai Gelam Subdistrict 97.9 hectares per year, and to the east towards Kumpeh Ulu District, amounting to 31.5 hectares per year. The size of paddy fields and dryland agriculture threatened with conversion in 2033 is 1036.1 hectares. The Muaro Jambi District Government needs to pay special attention to the potential areas affected by the physical expansion of Jambi City.Â